An efficient ultra-thin chain-structured copper cobalt oxide/sulfide composite catalyst for electrochemical hydrogen generation. Issue 49 (3rd May 2016) - Gong, Yudong; Zhao, Yang; Chen, Yujin; Wang, Yizhi; Sun, Chunwen
Abstract : An ultra-thin chain-structured copper cobalt oxide/sulfide composite catalyst was prepared by hydrothermal method for HER. Abstract : The electroreduction of water for sustainable hydrogen production is an important process for clean energy technologies, such as water splitting and fuel cells. However, development of low-cost and efficient electrocatalysts for hydrogen evolution reaction (HER) is still a great challenge. Here we reported a kind of ultrathin chain-structured CuCo2 O4 (CCO) and sulfured CuCo2 O4 (S-CCO) for HER with excellent activity and good durability in alkaline solution. At a current density of 10 mA cm −2, S-CCO nanocomposite catalyst only need an overpotential of 154 mV ( vs. RHE), whereas chain-structured CCO need an overpotential of 490 mV. It demonstrates that sulfured treatment is an effective approach to enhance the catalytic activity of oxide for HER.